Dinah Shore at Wake Forest United Way event - (:unkn) unknown (Z. Smith Reynolds Library, 1986)
Photos dated summer 1986
Dinah Shore chats with two Wake Forest cheerleaders (male) and Demon Deacon.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth